Pengembangan Media Video Pembelajaran Rias Fantasi di Jurusan Tata Kecantikan SMK Negeri 6 Padang - Delanda, Meisy Saskia; Hayatunnufus (Universitas Negeri Jakarta, 2023)
The purpose of this study was to develop learning video media and determine their validity, practicality, and effectiveness for fantasy makeup lessons with various themes at SMK Negeri 6 Padang. This research was a research and development study using the 4-D approach. The population consisted of 36 10th-grade KCII beauty care students at SMK Negeri 6 Padang during the 2022/2023 academic year. Data collection used a questionnaire. Data analysis involved calculating video assessment scores from the questionnaire and categorizing them using a t-test. The results of this study indicate that the video was developed using the 4-D development model. The video's validity was assessed by media experts at 0.90, and its material validity was assessed at 0.92, categorizing it as valid. The video's practicality test, based on teacher responses, scored 97%, categorizing it as very practical, and the student responses scored 80.91%, categorizing it as very practical. The effectiveness test, based on pre-test results, scored 38.88%, and post-test results scored 91.66%, categorizing it as effective for use at SMK Negeri 6 Padang City. These results indicate that the video is suitable, practical, and effective for use as teaching material in the classroom.